The Townsite Formation: An Aborted Rift Setting in the Yellowknife Greenstone Belt, N.W.T. - Finnigan, Craig S. (Scholarship@Western, 2000)
The Townsite Formation is a felsic unit separating the Crestaurum and Yellowknife Bay Formations of the mafic dominated Kam Group. Previous workers have divided the Townsite Formation into the Niven Lake, Brock, and Vee Lake lenticles, separated by Proterozoic faults. While substantiating the general similarity of the lithologies present in these lenticles, the mapping carried out in the present study identifies felsic porphyry phases contemporaneous with gabbro sills. This is indicated by “back veining” of the gabbro by porphyry and the absence of chill margins. In both the Niven Lake and Brock lenticles, injection of quartz feldspar porphyry has produced marginal hydrothermal breccias. These breccias give way northward into vented pyroclastic rocks in the Brock and Vee Lake lenticles. Vent proximal pyroclastic facies of the Vee Lake Lenticle grade laterally into more distal facies. The pillowed dacites identified by previous workers have basaltic to andesitic composition. The intrusive quartz feldspar porphyry bodies are dacitic in composition, while associated feldspar porphyries have more intermediate composition. Breccias, formed by quartz feldspar porphyry injecting older volcanic flows have andesitic to dacitic bulk composition. Trace element patterns of the feldspar porphyry and quartz feldspar porphyry intrusive phases indicate they were formed by melting of hydrated Kam Group volcanic flows. Partial melting is consistent with experimental results on the melting of hydrous greenstones and amphibolites. Similar patterns are shown by rocks formed by wet melting of juvenile crust both in modem and ancient rifting environments. Combining detailed mapping and analytical results of this study withprevious geochronological data the Townsite Formation is reinterpreted as having formed an aborted rift some twenty million years after cessation of Kam volcanism. Since the Townsite Formation is spatially related to mineralized segments of both the Campbell and Giant shear systems, it is likely that the intrusion of ...